Biological Agent Trichoderma asperellum and Its in Vitro Inhibitory Activity Against Mango Fruit Rot Pathogens - Gilang Vaza Benatar; Yeyet Nurhayati; Umi Kulsum (Jurnal Biologi Tropis, 2023)
Diseases are one of the major challenges in crop production which can lead to significant economic losses. Ironically, while having multiple negative impacts, synthetic chemical pesticides are considered the main strategy in tackling plant diseases. Trichoderma asperellum is one of the potential fungal species that can inhibit numerous plant diseases. This study reconfirmed the morphological characteristics of Trichoderma isolates obtained and identified it by molecular techniques. In addition, the inhibitory activity of the isolates was tested in vitro against the mango pathogens Colletotrichum asianum and Diaporthe pseudophoenicicola. The results showed that isolate T4 was identified as Trichoderma asperellum. Isolate T4 was able to inhibit C. asianum and D. pseudophoenicicola by 28.19% and 15.64%, respectively. Therefore, this isolate can be used as a biological agent to control plant pathogens in an environmentally friendly, sustainable manner, and as an alternative to synthetic chemical pesticides.